ANALISIS KELAYAKAN FINANSIAL MESIN PEMANEN TEBU CANE HARVESTER (STUDI KASUS PADA PT LAJUPERDANA INDAH SITE KOMERING) - Rika Agustina; Dwi Haryono; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aimed to analyses the productivity, thefinancial of feasibility and sensitivity of machine cane harvester. This research was a case study in PT Lajuperdana Indah Site Komering, South Sumatera. The data was collected in December 2016 andanalyzed by descriptive quantitative. The result of researchsuggested that big productivity machine cane harvester of 17.91 ton per hour work or 0.31 hectare per hour work or three hours of work to finish one hectare of land. The use of the machine cane harvester on PT Lajuperdana Indah Site Komering financially worth it to implement. The used of the machine cane harvester was sensitive at a change in the production of amounted to 19percent and increase in the17.58 percent but the value of payback period of the cane harvester was not sensitive.Key words: cane harvester machine, financially analyse, productivity.